Algorithm-Aided Design with Python: Analysis of Technological Competence of Subjects - Pontes, Thiago (2018)
Difficulties in learning computer programming for novices is a subject of abundant scientific literature. These difficulties seem to be accentuated in students whose academic choice is not computation, like architecture students. However, they need to study programming, since it is part of the new academic curricula. The results presented here are part of a PhD research, which investigates the achievement motivation and the acquisition and transfer of programming knowledge from an online environment designed on the basis of the 4C-ID instructional design model. These results are a sociodemographic analysis, and the technological competence of these subjects. We concluded that most of the students of our sample do not know how to auto assess their ICT expertise level, because they believed that they had sufficient computational knowledge for their needs. However, most of them told that they had difficulties creating codes. However, they recognized the importance of learning to program, thought it was valuable for architectural students, and felt motivated to acquire this new skill.